Stable high efficiency two-dimensional perovskite solar cells via cesium doping - Zhang, Xu; Ren, Xiaodong; Liu, Bin; Munir, Rahim; Zhu, Xuejie; Yang, Dong; Li, Jianbo; Liu, Yucheng; Smilgies, Detlef-M.; Li, Ruipeng; Yang, Zhou; Niu, Tianqi; et al. (Energy & environmental science, 2017)
Two-dimensional (2D) organic–inorganic perovskites have recently emerged as one of the most important thin-film solar cell materials owing to their excellent environmental stability. The remaining major pitfall is their relatively poor photovoltaic performance in contrast to 3D perovskites. In this work we demonstrate cesium cation (Cs + ) doped 2D (BA) 2 (MA) 3 Pb 4 I 13 perovskite solar cells giving a power conversion efficiency (PCE) as high as 13.7%, the highest among the reported 2D devices, with excellent humidity resistance. The enhanced efficiency from 12.3% (without Cs + ) to 13.7% (with 5% Cs + ) is attributed to perfectly controlled crystal orientation, an increased grain size of the 2D planes, superior surface quality, reduced trap-state density, enhanced charge-carrier mobility and charge-transfer kinetics. Surprisingly, it is found that the Cs + doping yields superior stability for the 2D perovskite solar cells when subjected to a high humidity environment without encapsulation. The device doped using 5% Cs + degrades only ca. 10% after 1400 hours of exposure in 30% relative humidity (RH), and exhibits significantly improved stability under heating and high moisture environments. Our results provide an important step toward air-stable and fully printable low dimensional perovskites as a next-generation renewable energy source.